(untitled) (The Review of Diabetic Studies, 2025)
Prevention of chronic energy Deficiency (CED) is still a challenge for developing countries like Indonesia. The CED has been included by the government in the national target in the 2015-2030 Sustainable Development Goals (SDGs) and target for pregnant women with CED is 5%. This was literature study aims to identify a variety of evidence about CED prevention strategies. This was is a literature study derived from search results on three electronic databases, namely Pubmed, Science Direct, Elsvier and Google Scholar. The journal references used as references are 12 journals that are relevant to the topic of this literature study. We did a journal of observational studies published from 2016 to 2022. The include studies Variables that have a relationship with chronic energy deficiency in pregnant women are diet, nutrient intake, food abstinence, socio-culture, economy, parity, knowledge, body mass index, early marriage. Prevention in overcoming the factors that cause CED is carried out with preventive feeding approaches, village head leadership approaches. Utilization of health facilities, the role of midwives and the role of husbands on the effectiveness of empowering pregnant women in efforts to treat CED and intercultural caring method. Prevention with the use of media that can, and CED prevention models in adolescents using Websites. Futher studies observing From 12 articles reviewed there were 2 articles with combine a behavioral approach, where 1 article discussed the influence of leadership in the area. The transcultural approach does not exist in CED so research related to this is urgently needed.